The dynamic assessment of language learning - Hasson, Natalie (London Routledge, 2018)
"This is a practical, accessible manual for Speech and Language Therapists, Educational Psychologists and Educators who assess children with language impairments, explaining how and why to implement Dynamic Assessment and gives you a huge range of ready-to-use, practical tools. Where normal assessments simply identify deficits, Dynamic Assessment also identifies the child's potential to learn by allowing for prompts from you, during the assessment, thus far better informing your decisions about appropriate interventions and strategies to help the children you work with."--Provided by publisher.
"A Speechmark book"--Cover.
Includes bibliographical references.
Keywords: Language disorders in children -- Diagnosis; Language arts -- Ability testing; Dynamic assessment (Education)